Degeneration and regeneration of cutaneous sensory nerve formations - Dubový, P; Aldskogius, H (Microscopy research and technique, 1996)
Auxiliary structures of the cutaneous sensory nerve formations (SNF) are dependent on sensory innervation during their critical period of development. Denervation of mature cutaneous corpuscles results in survival of the terminal Schwann cells and the capsular structures which are probably responsible for successful reinnervation of the cutaneous SNF. In addition, the basal lamina tubes of Schwann cells are connected with the terminal Schwann cells and play an important role in the guidance of regrowing axons to their original targets. Long-lasting denervation causes atrophic changes of the terminal Schwann cells and alterations of their molecular equipment. These atrophic changes in the terminal Schwann cells may be responsible for erroneous reinnervation of cutaneous SNF. A population of the cutaneous Merkel cells surviving denervation may also serve as targets for regrowing sensory axons. The basal laminae of terminal Schwann cells are produced under control of the sensory terminals during maturation of cutaneous SNF. In adult animals, the basal laminae are capable of stimulating differentiation of migrated Schwann cells to the terminal Schwann cells without the presence of the sensory terminals. Nonspecific cholinesterase (nChE) is secreted by the terminal Schwann cells and is attached to their extracellular matrix. The synthesis of these molecules in adult animals is not influenced by the sensory terminals. However, the presence of nChE molecules is associated with living terminal Schwann cells. Fetal orthotopically grafted dorsal root ganglion (DRG) neurons have the ability to reinnervate cutaneous SNF of adult hosts. When cutaneous areas are denervated, axons from adjacent sensory nerves may extend collateral branches into this area. The capacity for such extension is dependent on: (1) type of sensory nerve ending, C and A delta fibers having significantly greater capacity than sensory axons of larger caliber; (2) age of the animal, immature animals generally showing a greater capacity for collateral sprouting; (3) the state of the adjacent axons, those already in a growth mode being more capable than "resting" ones; and (4) the regional and mechanical conditions at the site of denervation, hindpaw skin being much less extensively reinnervated by collateral fibers than that of the trunk.
Keywords: Mechanoreceptors; Ganglia, Spinal; Merkelovy buňky; axony; kůže; zvířata; Rats; senzorická ganglia; Skin; Schwann Cells; transplantace fetální tkáně; Axons; regenerace nervu; Fetal Tissue Transplantation; krysa rodu Rattus; Animals; Ganglia, Sensory; spinální ganglia; Schwannovy buňky; mechanoreceptory; Merkel Cells; Nerve Regeneration